Strategi Humas dalam Upaya Meningkatkan Citra Perguruan Tinggi - Seprika Nur Andini; Adam Saleh; Selfiana Safitri; Elvi Royani; Tri Husnul Hasanah (TADRIBUNA: Journal of Islamic Education Management, 2025)
Public Relations strategy plays an important role in efforts to improve the image of higher education in the eyes of the public. This research is motivated by the importance of a positive image of higher education for the reputation and trust of the public. The purpose of this study is to analyze effective human strategies in efforts to improve the image of higher education. The method used is a library research that analyzes public relations theory and practice. The results of this study provide valuable guidance for Public Relations practitioners in higher education to improve the image of their institutions effectively through transparent communication with stakeholders, utilization of media (mass and social) to disseminate positive information, building good relationships with internal and external publics, and responsive crisis management. Thus, an integrated public relations strategy that includes these four aspects is proven effective in building a positive and competitive image of higher education.